Analisis Pendapatan Petani Kelapa Sawit dalam Meningkatkan Kesejahteraan Ekonomi Keluarga di Nagari Bawan Kabupaten Agam - Rahmidatul Annisa; Khadijah Nurani (Transformasi: Journal of Economics and Business Management, 2024)
The background of this study stems from a number of issues, including the inability of oil palm farmers to make ends meet financially, the impact of their reliance on oil palm income on the well-being of their families, and the relationship between oil palm farmers' income and the price at which Palm Fruit Bunches (FFB) are sold in Nagari Bawan, Kabupaten Agam. Nonetheless, a lot of farmers continue to struggle with a shortage of funding when it comes to running oil palm plantations and boosting the output of palm fruit bunches (FFB). A qualitative descriptive research approach is used, and it involves gathering research objects based on field data. Direct observation and interviews with oil palm farmers in Nagari Bawan, Kabupaten Agam, were used to gather data. The Nagari Bawan administration (Nagari Secretariat) and thirteen oil palm plantation owners were the research's primary sources of information about the circumstances and state of the study in Nagari Bawan, Kabupaten Agam. According to the author's study findings in Nagari Bawan, Kabupaten Agam, income indicators such as monthly income, employment, and family responsibilities may be used to analyze oil palm farmers' income in order to improve the economic welfare of their families. This indicates that oil palm growers are looking for side employment since their revenue is insufficient to cover their expenses.